Capacitive‐Type Two‐Axis Accelerometer with Liquid‐Type Proof Mass. (14th April 2020) - Won, Dong‐Joon; Huh, Myoung; Lee, Sangmin; Park, Usung; Yoo, Dongwoo; Kim, Joonwon
Abstract: Utilizing the advantages of a liquid metal (LM) (i.e., mercury) and its electro‐mechanical properties (i.e., high density, high surface tension, and high electrical conductivity), a novel capacitive‐type two‐axis accelerometer is proposed. The device employs a liquid‐type proof mass (i.e., liquid metal droplet) and is located in a cone‐shaped guiding channel. The Laplace pressure induced by the guiding channel and the LM droplet in the device acts as a spring due to the high surface tension of LM. To accurately set the spring constant of the device, a 2D mathematical model is established. Based on this mathematical model, the influence of the channel shape on device sensitivity is analyzed. Despite measuring the two‐axis accelerations using a single proof mass, the accelerometer yields a cross‐axis sensitivity of less than 1% for the x ‐ and y ‐axes. The accelerometer demonstrates an output similar to that of a reference accelerometer for a randomly applied acceleration. Owing to the nature of the liquid‐type proof mass, even if it is destroyed, its functionality is recovered by simply shaking the accelerometer. Finally, a 1.4% change in the accelerometer output is observed in the 15 000‐cycle test, and the device is applied to a maze escape game for verification. Abstract : Utilizing the advantages of a liquid metal (i.e., mercury) and its electro‐mechanical properties (i.e., high density, high surface tension, and high electrical conductivity), a novel capacitive‐type two‐axis accelerometer is proposed. Owing to the nature of the liquid‐type proof mass, even if it is destroyed, its functionality is recovered by simply shaking the accelerometer.